1997
DOI: 10.1523/jneurosci.17-19-07404.1997
|View full text |Cite
|
Sign up to set email alerts
|

All-or-None Ca2+Release from Intracellular Stores Triggered by Ca2+Influx through Voltage-Gated Ca2+Channels in Rat Sensory Neurons

Abstract: Ca2ϩ -induced Ca 2ϩ release (CICR) from intracellular stores amplifies the Ca 2ϩ signal that results from depolarization. In neurons, the amplification has been described as a graded process. Here we show that regenerative CICR develops as an all-or-none event in cultured rat dorsal root ganglion neurons in which ryanodine receptors have been sensitized to Ca 2ϩ by caffeine. We used indo-1-based microfluorimetry in combination with whole-cell patch-clamp recording to characterize the relationship between Ca 2ϩ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 78 publications
8
92
0
Order By: Relevance
“…22,23 To measure the contribution of CICR to the Ca 2+ transient after K + depolarization, we treated 17 neurons (3 large, 14 small, with comparable results) with ryanodine (10 μM; fig. 6A).…”
Section: Regulation Of Transient By Intracellular Ca 2+ Storesmentioning
confidence: 99%
“…22,23 To measure the contribution of CICR to the Ca 2+ transient after K + depolarization, we treated 17 neurons (3 large, 14 small, with comparable results) with ryanodine (10 μM; fig. 6A).…”
Section: Regulation Of Transient By Intracellular Ca 2+ Storesmentioning
confidence: 99%
“…We have observed that removal of Ca 2+ O depletes ryanodine-sensitive stores (both IP 3 R and RyR stores are coupled in DRG neurons [15]). The store-depletion paradigm that we used in these experiments required a prolonged incubation (30- Under physiological conditions, action-potential firing alone is sufficient to partially deplete intracellular stores [39]; however, activity itself activates voltage-gated Ca 2+ -influx pathways. As DRG neurons are not spontaneously active, we utilized the 0 Ca 2+ O paradigm to reproduce store-depletion independent of voltage-gated channel activation.…”
Section: Store-operated Channels May Underlie An Important Influx Mecmentioning
confidence: 99%
“…Neuronal function depends in part on release of calcium from the SER in response to [Ca 2+ ]i elevation (Usachev & Thayer, 1997, 1999a. Rapid calcium buffers immediately dampen much of the calcium influx through voltage-gated calcium channels while rapid release of calcium from the SER sustains depolarization-evoked increases in [Ca 2+ ]i.…”
Section: Consequences Of Age-related Changes In Serca Function: Agingmentioning
confidence: 99%
“…A unique feature of the CICR process, the "all or none" release of calcium from the SER, has been observed in peripheral sensory neurons (Usachev and Thayer, 1997). Using a combination of patch clamp and microfluorometry, [Ca 2+ ]i was elevated with graded step depolarizations of varied time length.…”
Section: Consequences Of Age-related Changes In Serca Function: Agingmentioning
confidence: 99%
See 1 more Smart Citation